First-line Treatment With Bendamustine and Rituximab for Old and Frail Patients With Aggressive Lymphoma: Results of the B-R-ENDA Trial. Issue 12 (1st December 2022) - Braulke, Friederike; Zettl, Florian; Ziepert, Marita; Viardot, Andreas; Kahl, Christoph; Prange-Krex, Gabriele; Korfel, Agnieszka; Dreyling, Martin; Bott, Alexander; Wedding, Ulrich; Reichert, Dietmar; de Wit, Maike; et al.
Abstract : The incidence of aggressive B-cell lymphomas increases with age, but for elderly or frail patients not eligible for doxorubicin-containing treatment standard therapy remains to be defined. In this prospective, multicenter, phase-2 B-R-ENDA trial, we investigated the feasibility, toxicity, and efficacy of 8 cycles rituximab combined with 6 cycles bendamustine (BR) in elderly or frail aggressive B-cell lymphoma patients: 39 patients aged >80 years and 29 patients aged 61–80 years with elevated Cumulative Illness Rating Scalescore >6 were included. Progression-free survival (PFS) and overall survival (OS) at 2 years were 45% (95% confidence interval [CI], 28%-61%) and 46% (28%-63%) for the patients age >80, as well 32% (13%-51%) and 37% (17%-57%) for frail patients age 64–80, respectively. In a preplanned retrospective analysis, we found no significant differences in PFS and OS comparing the outcome of the 39 patients age >80 years with 40 patients aged 76–80 years treated with 6xR-CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone) and 2 x rituximab in the RICOVER-60 trial (DSHNHL 1999-1, NCT00052936, EU-20243), yet we detected lower rates of infections and treatment-related deaths in the BR-treated patients. We demonstrate that older and frail patients with aggressive B-cell lymphoma who are not able to receive standard CHOP-based therapy can benefit from anthracycline-free therapy as a feasible and effective therapeutic option.